Efficient minimisation of Boolean functions - V. C., Prasad (MANCHESTER UNIV PRESS, 2008)
Quine Mc Cluskey's (QM) method is a popular method for minimisation of Boolean functions. This method is widely taught at undergraduate level. In this paper simple modifications are suggested to make it more efficient, They allow us to avoid repetitions in the QM method. Further, a minimal set of prime implicants is easily obtained.